REGIONAL AND MESOSCALE ECOGEOLOGICAL STUDYING AND MAPPING: THE BASIC PROBLEMS AND APPROACHES TO RESOLVE - LIUTA, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Improvement of environmental and geochemical researches and mapping quality demands perfection of their methodical maintenance. Ways of methodical maintenance improvement, first of all regarding criteria of an estimation of environment geochemical condition are offered.